The effects of static stretching and isometric strength on hamstring strength and flexibility asymmetry - Makaruk, H.; Makaruk, B.; Sacewicz, T. (Polish Journal of Sport and Tourism, 2010)
Considerable (over 10%) bilateral strength and flexibility asymmetry is one of the causes that increase the risk of hamstring injuries. The aim of this study was to define the effect of static stretching exercises and isometric strength exercises on bilateral asymmetry of hamstring strength and flexibility in athletes. Material and methods. Thirty athletes participated in the study. They were randomly divided into three groups, i.e. two experimental ones (isometric and stretching) as well as the control group. Training programmes lasted for 4 weeks and were carried out during an off-season. Two tests were conducted, i.e. strength test (peak torque - PT) and flexibility test (knee range of motion - ROM). Results. Significant decrease in the bilateral asymmetry of strength (by 4.19%) and flexibility (by 3.23%) was only observed in the group where stretching exercises were applied (p<0.05). Asymmetry in the isometric group did not change considerably (p>0.05). Conclusion. The assumption was that static stretching exercises ought to become an essential part of training programmes during an off-season.